The Effect of Joint Space on Midterm Outcomes After Arthroscopic Hip Surgery for Femoroacetabular Impingement. (May 2014) - Skendzel, Jack G.; Philippon, Marc J.; Briggs, Karen K.; Goljan, Peter
Background: Excellent short-term results have been reported after hip arthroscopic surgery to address femoroacetabular impingement (FAI). Purpose/Hypothesis: The purpose of this study was to determine if patients with narrow joint spaces had inferior outcomes at a postoperative minimum of 5 years and if they had a higher conversion rate to total hip arthroplasty (THA). The hypothesis was that patients with ≤2-mm joint spaces would report inferior outcomes and that patients with >2-mm joint spaces would have improved survivorship (no conversion to THA). Study Design: Cohort study; Level of evidence, 3. Methods: Between March 2005 and January 2008, prospectively collected data were analyzed for patients older than 18 years of age undergoing hip arthroscopic surgery for FAI. Radiographic measurements of joint space were collected, and hips were grouped as having preserved (>2 mm) or limited (≤2 mm) joint space. Outcome measures included the Western Ontario and McMaster Universities Arthritis Index (WOMAC), modified Harris Hip Score (MHHS), Hip Outcome Score (HOS) for activities of daily living and sports, and Short Form–12 (SF-12). Results: There were 559 patients included, 466 (83%) of whom were contacted. Fifty-four patients with limited joint spaces (86%) converted to THA, while only 63 patients with preserved joint spaces (16%) converted to THA. The mean survival time for patients with preserved joint spaces was 88 months (95% CI, 85-91 months), and the mean survival time for patients with limited joint spaces was 40.0 months (95% CI, 33.7-46.3 months) ( P = .0001). Complete follow-up outcome data were available on 323 patients, none of whom had THA, with a mean follow-up of 73 months. The mean postoperative HOS for activities of daily living and sports were significantly better in patients with preserved joint spaces (82 vs 62 [ P = .012] and 77 vs 47 [ P = .003], respectively) compared with those with limited joint spaces at a mean of 73 months postoperatively (range, 60-97 months). Conclusion: Hip arthroscopic surgery for FAI resulted in significantly better outcomes and activity levels at minimum 5-year follow-up in patients with preserved joint spaces. Hips with limited joint spaces converted to THA earlier than did those with preserved joint spaces.